2019
DOI: 10.3168/jds.2018-16011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of on-farm measurements for heat stress indicators on dairy cow productivity, female fertility, and health

Abstract: The aim of the present study was to quantify the effect of heat stress (HS) from different points in time on production, female fertility, and health traits. In this regard, on-farm measurements for temperature and relative humidity were combined into temperature-humidity indexes (THI), and merged with longitudinal cow traits from electronic recording systems. The study included traits from 22,212 Holstein cows kept in 15 large-scale dairy co-operator herds. Trait and meteorological data recording spanned a pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 67 publications
(81 reference statements)
3
39
0
2
Order By: Relevance
“…DuBois and Williams (105) examined seasonal incidence of retained placenta in a single herd, and found that the percentage of cows with a retained placenta (RP) doubled in the summer relative to the winter, and cows with an RP had an additional 24 days open compared with the reproductive performance of healthy cows. A recent study by Gernand et al (106) tied the relationship of RP and metritis more closely to increases in THI. With records from 22,000 cows, puerperal disorders and RP increased linearly with the average THI in the 5 days after calving.…”
Section: Effects Of Heat Stress During the Postnatal Period On Immunimentioning
confidence: 99%
“…DuBois and Williams (105) examined seasonal incidence of retained placenta in a single herd, and found that the percentage of cows with a retained placenta (RP) doubled in the summer relative to the winter, and cows with an RP had an additional 24 days open compared with the reproductive performance of healthy cows. A recent study by Gernand et al (106) tied the relationship of RP and metritis more closely to increases in THI. With records from 22,000 cows, puerperal disorders and RP increased linearly with the average THI in the 5 days after calving.…”
Section: Effects Of Heat Stress During the Postnatal Period On Immunimentioning
confidence: 99%
“…Heat stress causes changes in homeostasis and has been quantified by the measurement of milk production and physiological variables such as body temperature, respira tory rate, and behaviors of cows [23]. According to a study by Gernand et al [24], milk production is not affected by heat stress when mean THI values are under 68. However, milk production and feed intake begin to decline when be yond THI 68 [24,25].…”
Section: Experiments 2: Effects Of a Supplemental Dietary Mixture Of Pmentioning
confidence: 99%
“…The developed technology can affect most parameters of the microclimate and maintain within the specified limits temperature and relative humidity of air, air velocity, concentration of harmful gases (ammonia, carbon dioxide, and hydrogen sulfide), dust and microorganisms [3,4,6,7,8,10,12,14,15,19]. The technological process of a microclimate system with air conditioning includes such operations as heating, cooling, humidification, drying and purification of air from harmful gases, dust and microorganisms.…”
Section: Development Of Energy-saving Technology For Formation Of Optmentioning
confidence: 99%
“…The amount of metabolic energy yielding products other than the body's heat production is also reduced by so-called non-productive energy needs: the energy needs of the animal, consisting of thermoregulation, which is necessary to maintain constant body temperature, and the energy expended on movement [4, 6,12,14,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation